2021
DOI: 10.1109/access.2021.3101253
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Deep Learning Algorithms for Cardiothoracic Ratio Measurement

Abstract: Recent advances in machine learning have made it possible to create automated systems for medical image diagnosis. Cardiothoracic ratio (CTR) measurement, a common procedure for assessing cardiac abnormality in chest radiographs, has been investigated by several deep learning studies aiming to automate the process. However, of key consideration is whether automated CTR measurements by machine learning models can yield CTR values as accurately and consistently as trained human technicians on unseen data and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In our recent study [ 10 ], we reviewed the literature regarding anatomical segmentation in chest x-rays and observed that U-Net has emerged as a widely used model for chest x-ray and medical image segmentation tasks [ 12 , 13 ]. As the name suggested, the U-shape architecture consists of (1) an encoder that extracts features through successive convolutional layers that reduce the dimension of the inputs, and (2) a decoder that applies successive up-sampling operators to predict a high-resolution mask output.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent study [ 10 ], we reviewed the literature regarding anatomical segmentation in chest x-rays and observed that U-Net has emerged as a widely used model for chest x-ray and medical image segmentation tasks [ 12 , 13 ]. As the name suggested, the U-shape architecture consists of (1) an encoder that extracts features through successive convolutional layers that reduce the dimension of the inputs, and (2) a decoder that applies successive up-sampling operators to predict a high-resolution mask output.…”
Section: Methodsmentioning
confidence: 99%
“…First, we validated the proposed DL models [ 10 ] to find the best model results for clinical implementation, and then evaluated the best model for clinical use. To validate the DL models, we performed the experiment on our previous dataset with manual results that served as the reference and employed the models using the AI-assisted method [ 9 ], and calculated percentage difference of CTR values between AI’s and manual results, or CTR diff .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations